Molecular Qubits Based on Zwitterions with Close pKa Values and Comparable Charge-Transfer Energies: A Theoretical Analysis - González Santiago, Omar (Zenodo)
This theoretical analysis proposes zwitterionic compounds as molecular qubits. Organic zwitterions are characterized by functional groups with closely spaced pKa values, while inorganic or hybrid zwitterions exhibit comparable charge transfer energies between two internal centers. In organic systems, the strategic proximity of pKa values enables precise control over protonation states, facilitating the representation of quantum basis states |0⟩ and |1⟩, as well as superposition states within individual molecules. In inorganic systems, discrete quantum states arise from charge localization at distinct centers, with superposition resulting from partial charge delocalization. The essential characteristics of an ideal zwitterionic molecule for encoding quantum information are discussed. While the primary application lies in quantum computing, other potential uses are not excluded.